Colorectal cancer-related mutant KRAS alleles function as positive regulators of autophagy - Alves, Sara (2015)
The recent interest to modulate autophagy in cancer therapy has been hampered by the dual roles of this conserved catabolic process in cancer, highlighting the need for tailored approaches. Since RAS isoforms have been implicated in autophagy regulation and mutation of the KRAS oncogene is highly frequent in colorectal cancer (CRC), we questioned whether/how mutant KRAS alleles regulate autophagy in CRC and its implications. We established two original models, KRAS-humanized yeast and KRAS-non-cancer colon cells and showed that expression of mutated KRAS up-regulates starvation-induced autophagy in both. Accordingly, KRAS down-regulation inhibited autophagy in CRC-derived cells harboring KRAS mutations. We further show that KRAS-induced autophagy proceeds via up-regulation of the MEK/ERK pathway in both colon models and that KRAS and autophagy contribute to CRC cell survival during starvation. Since KRAS inhibitors have proven difficult to develop, our results suggest using autophagy inhibitors as a combined/alternative therapeutic approach in CRCs with mutant KRAS.